Improving Children's English Vocabulary Mastery Through The TGT Learning Model And Vocabulary Cards - Halimah Khoirun Ni’mah Rais; Umi Rachmawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Learning the language is very important, including learning English. However, based onresearch conducted by EF World Institute of Education English First announced the firstcomprehensive report, the on index English proficiency index in 44 English proficiencycountries in Indonesia is very low in the 34th place. One of the biggest factors in Englishlearning is that students need vocabulary mastery. In learning English in elementaryschool the understanding of English vocabulary is still difficult because teachers deliverlearning only by lecture methods, let alone the use of very minimal media, so because ofthat method teaching and learning process makes the students feel boring because itfeels monotonous. One way to make English learning effective is to use a learning modelthat can provide meaning and fun for students. Team Game Tournament learning modelbased on Vocabulary Card Media is expected to make students active and excited so thatstudents can easily understand the material studied.